Pewarnaan Titik r-Dinamis pada Graf Hasil Operasi Edge Corona - Adelia Putri Liowardani; Dafik Dafik; Arif Fatahillah (CGANT JOURNAL OF MATHEMATICS AND APPLICATIONS, 2020)
This research is a development of research on $r$-dynamic vertex coloring on simple, connected, and undirected graphs. The $r$dynamic vertex coloring on the graph $G$ is the $r$ point coloring of the $r$ graph so that the vertices of degree two on the $G$ graph have at least two different color neighbors. The $r$-dynamic vertex coloring is satisfied if it meets the conditions for $\forall v \in V(G)$, $|c(N(v))|$ $≥$ min$\{r,d(v)\}$. The chromatic number for the $r$-dynamic vertex coloring of the graph $G$ is denoted as $χ_r(G)$. In this study, we discuss the $r$-dynamic vertex coloring on the graph resulting from the edge corona operation on a path graph with a complete graph, a star graph, and a sweep graph. It is denoted that the result of the operation of edge corona graph $G$ and graph $H$ is $G \diamond H$. In this study, the results of the $r$-dynamic vertex coloring are described in the operation graph $P_n \diamond K_m$, $P_n \diamond S_m$, $P_n \diamond P_m$, and $P_n \diamond B_{(m,k)}